Perkawinan Sejenis Dalam Presfektif Aliran Eksistensialisme Dikaitkan Dengan Hak Asasi Manusia - Syuhada, Otong (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
A marriage is generally legalized in some countries for couples consisting of one male and one female. But similar marriage is a different matter. This type of marriage is often done between men and women and women. This marriage is considered as the right of the individual to shape his own life, so that anyone cannot forbid it, so does the existentialism flow which states that every individual is given the greatest freedom. Of course, this freedom makes an individual do things he thinks are right because it is from his own right as an individual. In HAM also states that the right to freedom of association contains elements of the right to freedom and social rights and freedom of religion shows the distinctive personal and collective rights, but if we examine it more deeply it is clear that freedom in question is freedom that has boundaries that must be met as well ; does it violate decency, religion, or the integrity of the nation? The purpose of this study is to find out same-sex marriage in the existentialism flow and to know the human rights perspective in criticizing same-sex marriage. This study uses a normative juridical approach and the nature of this research is descriptive analytical.Â